The performance of durum and bread wheat genotypes associated with yield and yield component under different water deficit conditions - Moayedi, Ali Akbar; Boyce, Amru Nasrulhaq; Barakbah, Syed Shahar (American-Eurasian Network for Scientific Information, Jordan, 2010)
Although drought stress has been well documented as an effective parameter in decreasing crop production in arid and semi arid regions, developing and releasing new varieties which are adaptable to water deficit conditions can be a constructive program to overcome unsuitable environmental conditions. The present study was carried out to study the performance of durum and bread wheat genotypes in relation to yield and yield component under different water deficit conditions. The experiment was laid out in split plot based on a complete randomized block design, with three replications at Mashhad Agricultural Research stations in Iran. Irrigation regimes were considered as the main plots and included four levels. Sub-plots were assigned to five wheat genotypes, four durum promising lines and a bread wheat cultivar. The number of spike m -2, number of kernel spike -1 1000-kernel weight, plant height, day to maturity, maturity duration, harvest index, and grain yield were highly significant (P<0.01) affected by water deficit conditions and genotype effects. In addition to this, the effect of genotype on the biological and grain yield was significant (P<0.05). It was observed that water limitation significantly decreased plant height in the early water deficit, while water limitation during double ridge to anthesis reduced the number of spike m -and2 number of kernel spike -1. Besides, water deficit condition at post-anthesis decreased the number of day to maturity, maturity duration, 1000-kernel weight, harvest index and grain yield. Chamran bread wheat cultivar and a promising durum wheat genotype (RASCON37/BEJAH7) produced the highest values for the plant height, kernel numbers, harvest index traits and lastly grain yield compared to all the other genotypes. Â© 2010, INSInet Publication.